O PAPEL DOS CONTRATOS REAIS NOS PAÍSES DO BRICS: O CONTRATO DE MÚTUO - Saccoccio, Antonio (Revista da AJURIS - Qualis A2, 2020)
THE ROLE OF THE REAL CONTRACTS IN THE BRICS COUNTRIES: THE CONTRACT OF LOAN ÁREA(S): direito privado; direito contratual; direito romano. RESUMO: O presente trabalho pretende examinar a evolução da natureza do contrato de mútuo de contrato real para contrato consensual, a partir do Direito romano, a fim de focar na análise dos ordenamentos jurídicos dos países integrantes do bloco Brics. ABSTRACT: The present work aims to examine the evolution of the nature of the loan contract from a real contract to a consensual contract, based on Roman law, in order to focus on the analysis of the legal systems of the countries that are part of the BRICS bloc. PALAVRAS-CHAVE: contrato de mútuo; contratos reais; Brics. KEYWORDS: contract of loan; real contracts; Brics. SUMÁRIO: 1 O mútuo no Direito romano: a base do sistema jurídico; 2 O mútuo na tradição civilista: da glosa ao humanismo; 3 O mútuo na América Latina: os dois modelos diferentes; 4 Os países do Brics; Conclusão. SUMMARY: 1 The loan in roman law: the foundation of the legal system; 2 The loan in the civilian tradition: from the glossa to the humanism; 3 The loan in Latin America: the two different models; 4 The Bric’s countries; Conclusion.